Implementasi Metode Naive Bayes Untuk Diagnosis Penyakit Kambing (Studi Kasus : UPTD. Pembibitan Ternak dan Hijauan Makanan Ternak Kec. Singosari Malang) - Healtho Brilian Argario; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Goat breeding is the main commodity in the Technical Implementation Unit of Livestock Breeding and Forage of Livestock Feed (UPT PT and HMT) Kec. Singosari Malang. Based on East Java Governor Regulation No. 130 of 2008 on Organization and Working Procedure of Technical Implementation Unit of Livestock Service Office of East Java Province, one of the tasks of UPT PT and HMT Malang is to cooperate with livestock groups, and provide livestock seed support, especially goats. Goat cattle business will experience constraints when the goat is infected with the disease. For the target group that wants to consult with the UPT and HMT should contact the agency and the doctor will come to check. This is less effective considering the distance, length of travel time and the number of animals controlled by the agency. Therefore, researchers want to make intelligent computing that can be applied to the laptop or personal computer in order to help the group of livestock assisted UPT PT and HMT Malang to diagnose the disease. The method used in this research is by Naive Bayes method. Input is a symptom that occurs in the field and the output of the diagnosis and treatment advice. The result of system testing accuracy with Naive Bayes method is 90%. With the results of such precision, the method of Naive Bayes has a good.